The Effects of Education on Job Satisfaction Among Young Workers in Vietnam - Quy Thanh, Nguyen; Anh, Nguyen Thuy; Anh, Tran Lan; Bich, Nguyen Thi (VNU Journal of Science: Education Research; Vol 36 No 1DO - 10.25073/2588-1159/vnuer.4373, 2020)
Using secondary data from the School-to-Work Transition Survey-SWTS in 2012-2015, this study examines the effects of education on job satisfaction among young workers in Vietnam. Both descriptive statistics and logistic regression analysis were used in the study. Our econometric analysis shows that individuals with higher levels of education are less likely to have lower levels of jobs satisfaction. The result is robust even after controlling for many important controlling variables such as occupations, wages and economic household status. This finding can be explained that those with better education tend to have higher expectation for their work, which in turn can have lower levels of job satisfaction. Our research finding implies that while better education can improve wage earnings, it might not improve job satisfaction.